Modern Processes in the Lexical System of the Russian Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the main trends in the development of the lexical system of modern Russian. Special attention is paid to the processes of neologization, borrowing, word-formation activity, democratization, and digitalization of the lexicon. The analysis is based on modern media, Internet, and colloquial sources. The main types of lexical innovations, their causes, and consequences for the language system and communicative practice are identified.